2022
DOI: 10.4110/in.2022.22.e36
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone, but Not Vitamin D or A, Dampens the Inflammatory Neutrophil Response to Protect At-risk COVID-19 Patients

Abstract: Dexamethasone (DEX) was the first drug shown to save lives of critically ill coronavirus disease 2019 (COVID-19) patients suffering from respiratory distress. A hyperactivated state of neutrophils was found in COVID-19 patients compared to non-COVID pneumonia cases. Given the beneficial effects of DEX in COVID-19 patients, we investigated the effects of DEX and of other immunomodulatory drugs vitamin D3 (VD3) and retinoic acid (RA) on neutrophil function. DEX, but not VD3 or RA, significantly inhibited all tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Neutrophils cultured with dexamethasone showed reduced NET formation, after stimulation with PMA [98].…”
Section: Nox-dmentioning
confidence: 95%
See 1 more Smart Citation
“…Neutrophils cultured with dexamethasone showed reduced NET formation, after stimulation with PMA [98].…”
Section: Nox-dmentioning
confidence: 95%
“…PE is characterized by a state of systemic inflammation where platelet abnormalities occur. It has been shown that dexamethasone significantly inhibited degranulation, intracellular ROS production, CXCL8 release, and neutrophil NETosis in patients with severe COVID-19 pneumonia [98]. Dexamethasone has been shown to inhibit Staphylococcus aureus-induced NET formation via upregulation of TLR2 and TLR4 receptors [156], this could mean that Dexamethasone induces vital NETs.…”
Section: Therapeutic Approaches To Inhibit Net Formation In Pementioning
confidence: 96%
“…Nonetheless, with more information on the pathophysiology of COVID-19, it was hypothesized that the anti-inflammatory properties of corticosteroids may suppress hyperinflammation and modulate the immune-mediated damages following SARS-CoV-2 infection ( 151 ). Dexamethasone (DEX), a glucocorticosteroid used primarily to treat inflammatory and autoimmune diseases, was found to dampen the inflammatory neutrophil response associated with severe COVID-19 in vitro ( 152 ). DEX was examined as treatment in a controlled, randomized, open-label RECOVERY trial ( NCT04381936 ; Table 2 ) ( 153 ).…”
Section: Immune-based Therapiesmentioning
confidence: 99%
“…The pathophysiological role of NETosis in neutrophil infection immunity is not entirely understood, but it is an essential mechanism for neutrophil anti-infection immunity ( Ou et al, 2021 ). Despite the crucial role that NETosis plays in antimicrobial processes, excessive NETosis can lead to severe tissue damage and exacerbation of inflammation ( Hafkamp et al, 2022 ). It is noteworthy that NETosis causes thrombosis, which exacerbates COVID-19, cancer, acute myocardial infarction, and ischemic stroke ( Wang H. et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%